Effect of polyarylene ether nitriles on processing and mechanical behaviors of phthalonitrile‐epoxy copolymers and glass fiber laminated composites. Issue 6 (11th June 2012) - Zhao, Xin; Guo, Heng; Lei, Yajie; Zhao, Rui; Zhong, Jiachun; Liu, Xiaobo
Abstract A series of copolymers and glass fiber composites were successfully prepared from 2, 2‐bis [4‐(3, 4‐dicyanophenoxy) phenyl] propane (BAPh), epoxy resins E‐44 (EP), and polyarylene ether nitriles (PEN) with 4, 4′‐diaminodiphenyl sulfone as curing additive. The gelation time was shortened from 25 min to 4 min when PEN content was 0 wt % and 15 wt %, respectively. PEN could accelerate the crosslinking reaction between the phthalonitrile and epoxy. The initial decomposition temperatures (Ti) of BAPh/EP copolymers and glass fiber composites were all more than 350°C in nitrogen. The Tg of 15 wt % PEN glass fiber composites increased by 21.2°C compared with that of in comparison with BAPh/EP glass fiber composite. The flexural strength of the copolymers and glass fiber composites reached 119.8 MPa and 698.5 MPa which increased by 16.6 MPa and 127.3 MPa in comparison with BAPh/EP composite, respectively. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013